Serum level of soluble interleukin‐2 receptor is positively correlated with metabolic tumor volume on (18)F‐FDG PET/CT in newly diagnosed patients with diffuse large B‐cell lymphoma - Senjo, Hajime (Cancer Med, 2019)
Diffuse large B‐cell lymphoma (DLBCL) is the most frequent subtype of non‐Hodgkin lymphoma. High total metabolic tumor volume (TMTV) calculated using (18)F‐FDG PET/CT images at diagnosis predicts poor prognosis of patients with DLBCL. However, high cost and poor access to the imaging facilities hamper wider use of (18)F‐FDG PET/CT. In order to explore a surrogate marker for TMTV, we evaluated the correlation between the serum levels of soluble interleukin‐2 receptor (sIL‐2R) and TMTV in 64 patients with DLBCL, and the results were verified in an independent validation cohort of 86 patients. Serum levels of sIL‐2R were significantly correlated with TMTV. ROC analysis revealed that the cutoff value of TMTV ≥150 cm(3) or sIL‐2R ≥ 1300 U/mL could predict failure to achieve EFS24 with areas under the curve (AUC) 0.706 and 0.758, respectively. Each of TMTV ≥150 cm(3) and sIL‐2R ≥1300 U/mL was significantly associated with worse 5‐year overall survival and event‐free survival. Importantly, each of sIL‐2R <1300 U/mL or TMTV <150 cm(3) identified patients with favorable prognosis among NCCN‐IPI high‐intermediate and high‐risk group. Serum level of sIL‐2R represents a convenient surrogate marker to estimate metabolic tumor burden measured by (18)F‐FDG PET/CT that can predict treatment outcomes of patients with DLBCL.